Taxpayer's Religiosity, Religion, and the Perceptions of Tax Equity: Case of South Korea - Jun, Byung Wook (Religions, 2018)
The purpose of this study is to investigate the effect of religiosity and religion on tax equity. Most prior studies have argued that higher taxpayers' religiosity reduces tax evasion and increases the level of tax morale. Various studies have also shown that tax evasion and morale vary with perceptions of tax equity, including exchange, horizontal, and vertical equities. However, the relationship between religiosity and tax equity has not been studied actively. Especially in Korea, there has been considerable debate about the implementation of taxation for clergies. Therefore, the relationship between religiosity and tax equity will be analyzed clearly using Korean survey panel data. The results of this study show that religiosity and religion do not affect exchange and horizontal equity; however, each religion affects vertical equity. This implies that economic and social incentives are more effective than religiosity and religion on taxpayers' tax evasion or morale.